Is a switch to a different electronic health record associated with a change in patient satisfaction?. (1st May 2020) - North, Frederick; Pecina, Jennifer L; Tulledge-Scheitel, Sidna M; Chaudhry, Rajeev; Matulis, John C; Ebbert, Jon O
Abstract: Objective: Financial impacts associated with a switch to a different electronic health record (EHR) have been documented. Less attention has been focused on the patient response to an EHR switch. The Mayo Clinic was involved in an EHR switch that occurred at 6 different locations and with 4 different "go-live" dates. We sought to understand the relationship between patient satisfaction and the transition to a new EHR. Materials and Methods: We used patient satisfaction data collected by Press Ganey from July 2016 through December 2019. Our patient satisfaction measure was the percent of patients responding "very good" (top box) to survey questions. Twenty-four survey questions were summarized by Press Ganey into 6 patient satisfaction domains. Piecewise linear regression was used to model patient satisfaction before and after the EHR switch dates. Results: Significant drops in patient satisfaction were associated with the EHR switch. Patient satisfaction with access (ease of getting clinic on phone, ease of scheduling appointments, etc.) was most affected (range of 6 sites absolute decline: -3.4% to -8.8%; all significant at 99% confidence interval). Satisfaction with providers was least affected (range of 6 sites absolute decline: -0.5% to -2.8%; 4 of 6 sites significant at 99% confidence interval). After 9-15 months, patient satisfaction with access climbed back to pre-EHR switch levels. Conclusions: Patient satisfaction in several patient experience domains dropped significantly and stayed lower than pre–"go-live" for several months after a switch in EHR. Satisfaction with providers declined less than satisfaction with access.